2006
DOI: 10.1080/09540260600658262
|View full text |Cite
|
Sign up to set email alerts
|

After the tsunami: A story from Sri Lanka

Abstract: Children and adolescents are one of the very vulnerable groups in any disaster situation. Not only did around 10,000 children die in the tsunami in Sri Lanka, but the survivors experienced a number of symptoms. Children and adolescents were often not allowed to grieve, as information on their parents' and family members' deaths were withheld from them in order to protect them. Fear of recurrence and separation anxiety was related to school refusal. In addition, displacement and within-country migration led to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…In 2004, Sri Lanka experienced an unexpected tsunami causing a death toll of 35,000 [1], including 10,000 children [2], resulting in bereavement, lack of social and family support and significant economical insecurity [3, 4]. Previous disaster research revealed significant mental health problems among children exposed to major disasters including posttraumatic stress disorder (PTSD) [5,6,7,8,9,10,11,12,13], behavioral problems [14], anxiety [6], depression [15, 16], fears [17], and learning difficulties [18].…”
Section: Introductionmentioning
confidence: 99%
“…In 2004, Sri Lanka experienced an unexpected tsunami causing a death toll of 35,000 [1], including 10,000 children [2], resulting in bereavement, lack of social and family support and significant economical insecurity [3, 4]. Previous disaster research revealed significant mental health problems among children exposed to major disasters including posttraumatic stress disorder (PTSD) [5,6,7,8,9,10,11,12,13], behavioral problems [14], anxiety [6], depression [15, 16], fears [17], and learning difficulties [18].…”
Section: Introductionmentioning
confidence: 99%
“…It is thus generally important to include informants of different genders and ages (Dahlberg et al, 2008). Grief is a normal response in the early aftermath of a disaster, but is at the same time culturally specific (Nikapota, 2006; Pérez-Sales et al, 2005). Autobiographies from the Eastern part of the world would probably have contributed to greater variations in the data, which would have been an advantage to the study.…”
Section: Methodsmentioning
confidence: 99%
“…Most cultures have their own particular grief rituals/ceremonies, and these play an important role in the trauma recovery (Lundin, 1982; Pérez-Sales, Cervellón, Vázquez,Vidales, & Gaborit, 2005). Cultural norms in Sri Lanka dictated that the information that next of kin had been killed in the tsunami catastrophe was withheld from the relatives, thus preventing them from mourning (Nikapota, 2006). However, when screened for complicated grief nearly half of the project liberty service recipients showed symptoms of complicated grief 18 months after September 11.…”
Section: Introductionmentioning
confidence: 99%
“…communities, families and children "internalised" many of the fears and anxieties linked to the loss of family and homes, suggesting the need to consider and study further the "contagious" effects of trauma caused by such natural disasters [21, 24,25]. As shown by a study on collective trauma in northen Sri Lanka, exposure to conflict, war and disaster situations impacts on fundamental family and community dynamics, which results in changes at a collective level [26].…”
Section: Discussionmentioning
confidence: 99%